Does ownership moderate the effects of size on pension funds’ efficiency and investment performance? - Lintang Putri; Imanuel Madea Sakti; Apriani Dorkas Rambu Atahau (Jurnal Keuangan dan Perbankan, 2020)
This study aims to explore the effect of specific characteristics of pension funds: size, efficiency, and ownership on pension fund performance. Specifically, it aims to obtain empirical evidence of whether pension fund ownership moderates the effect of size and efficiency on pension fund performance. We use annual financial statements obtained from the Indonesian Pension Fund Association (ADPI) for the period 2013-2017. The sampling technique generates the final sample of 167 pension funds and number of observations 835 firm-year. Using panel regression, we find that pension fund size has no significant positive effect on pension funds efficiency and investment performance. In addition, ownership does not moderate the effect of pension fund size on the efficiency and investment performance of pension funds. We suggest that large pension funds do not necessarily generate revenues higher than investment costs. Hence, our results inform the Financial Service Authority (FSA) to encourage pension funds to utilize their large size to generate higher revenues and exhibit more positive performance. JEL Classification: G22, G32DOI: https://doi.org/10.26905/jkdp.v24i3.4108